The relationship between food insecurity and mental health: do resilience factors mediate this relationship? - Intagliata, Maeve C. (Kansas State University, 2023)
Food insecurity continues to rise as a significant public health concern in the United States, affecting millions daily. Literature and studies of food insecurity have identified correlations between food insecurity and mental health; however, understanding to what extent resilience factors mediate this relationship remains lacking among food insecurity literature, specifically among rural populations. This study uses data from the multi-state research project, NC-1171 Interactions of Individual, Family, Community, and Policy Contexts, often referred to as “Rural Families Speak about Health” [RFSH], to better understand the correlation between food insecurity and mental health and the extent to which that relationship’s mediation occurs by specific resilience factors of parental alliance, adult physical health status, child behavior, and family routines, among rural, low-income families through the lens of Family Systems Theory (Minuchin, 1974) and Family Stress Theory (Hill, 1958). Data were analyzed using hierarchical multiple regression analysis for 444 rural mothers with low incomes to understand the relationship between variables. Results indicated a significant relationship between food insecurity and maternal mental health. No significance was found to report family routines as a mediating factor. The study findings suggest that parental alliance, adult physical health, and child behaviors are resilience factors that mediate the relationship between food insecurity and maternal depression but can also manifest as risk factors in worsening this relationship among rural, low-income households. The findings and results are of interest to practitioners, policymakers, and researchers and are reported.
Keywords: Food insecurity; Resilience; Rural; Low-income; Mental health